2015
DOI: 10.1021/acs.joc.5b02093
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Keto(hetero)aryl Benzox(thio)azoles through Base Promoted Cyclization of 2-Amino(thio)phenols with α,α-Dihaloketones

Abstract: An interesting base-promoted protocol for the synthesis of 2-keto(hetero)aryl benzox(thi)azoles has been developed. Starting from commercially available 2-amino(thio)phenols and α,α-dihaloketones, moderate to good yields of the corresponding heterocycles can be achieved. Notably, only EtNH2 was required as the promoter here, and the reaction can be easily performed on a large scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…Aryl-substituted azoles and their derivatives are popular structural scaffolds found in miscellaneous series of biologically active compounds, agricultural chemicals, pharmaceutical chemicals, and organic materials. [1][2][3][4][5] These skeletons were previously synthesized via the reaction between metalloheteroarenes and haloarenes, or metalloarenes and haloheteroarenes, hence experiencing disadvantages with regard to green chemistry points of view. 3 Recently, different strategies for these structures have been developed and mentioned in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Aryl-substituted azoles and their derivatives are popular structural scaffolds found in miscellaneous series of biologically active compounds, agricultural chemicals, pharmaceutical chemicals, and organic materials. [1][2][3][4][5] These skeletons were previously synthesized via the reaction between metalloheteroarenes and haloarenes, or metalloarenes and haloheteroarenes, hence experiencing disadvantages with regard to green chemistry points of view. 3 Recently, different strategies for these structures have been developed and mentioned in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting alternative access to 2‐keto (hetero)aryl benzoxazoles 10 or 29 can be achieved by the use of α,α‐dihaloketones 43 as substrates. He et al demonstrated that the reaction between α,α‐dihaloketones 43 and 2‐aminophenols 42 is promoted by the use of Et 2 NH as base in dimethylformamide at 90°C yielded the compound 10 or 29 (Scheme ). A sequential synthesis of dibromoketones 43 was achieved starting from the corresponding substituted phenylacetylene and N ‐bromosuccinimide, followed by Et 2 NH, which promoted the cyclization reaction (Scheme ).…”
Section: Synthesis Of 2‐keto‐annulated Oxazolesmentioning
confidence: 78%
“…A variety of synthetic approaches to α‐keto (hetero)aryl benzoxazoles are based on the reaction of 1,1‐dibromoethenes, α,α‐dihaloketones, and alkynylbromides with 2‐aminophenols. The preparation of α‐keto (hetero)aryl benzoxazoles 10 or 29 was through the coupling reaction of 1,1‐dibromoethenes 40 with o ‐aminophenols 42 under the assistance of TBAF·3H 2 O and RuCl 3 complex.…”
Section: Synthesis Of 2‐keto‐annulated Oxazolesmentioning
confidence: 99%
“…An efficient synthetic method for 2‐keto(hetero)aryl benzox(thi)azoles 220 was demonstrated by He et al., in 2016 (Scheme ), employing α,α‐dihaloketones 221 (as one carbon source) and 2‐amino(thio)phenols under basic condition (Et 2 NH). Mechanistically, Et 2 NH would undergoes the mono‐nucleophilic substitution reaction with gem ‐dihaloketone 221 to generate the intermediate 221 a .…”
Section: The Gem‐dihaloketones In the Synthesis Of Heterocyclic Framementioning
confidence: 99%